2019
DOI: 10.3390/rs11212500
|View full text |Cite
|
Sign up to set email alerts
|

Towards Multiscale and Multisource Remote Sensing Mineral Exploration Using RPAS: A Case Study in the Lofdal Carbonatite-Hosted REE Deposit, Namibia

Abstract: Traditional exploration techniques usually rely on extensive field work supported by geophysical ground surveying. However, this approach can be limited by several factors such as field accessibility, financial cost, area size, climate, and public disapproval. We recommend the use of multiscale hyperspectral remote sensing to mitigate the disadvantages of traditional exploration techniques. The proposed workflow analyzes a possible target at different levels of spatial detail. This method is particularly benef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 67 publications
0
16
0
2
Order By: Relevance
“…Successful applications of UAS-based surveys in mineral exploration were used to explore rare earths using spectral imaging [10] and target uranium deposits using radiometric gamma survey [11]. UAS geophysical magnetic mapping was employed in exploration for iron, zinc, chromite, or gold deposits [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Successful applications of UAS-based surveys in mineral exploration were used to explore rare earths using spectral imaging [10] and target uranium deposits using radiometric gamma survey [11]. UAS geophysical magnetic mapping was employed in exploration for iron, zinc, chromite, or gold deposits [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Reflectance spectroscopy has shown an immense potential for fast, non-invasive mineral mapping. Several studies particularily demonstrated advances in reflectance hyperspectral imaging (in the following abbreviated as HSI) of REEs in natural materials from close-range scanning of drill-cores and outcrops or from drone-borne data of larger-scale areas (e.g., Boesche et al, 2015;Turner, 2015;Neave et al, 2016;Zimmermann et al, 2016;Booysen et al, 2019). However, an absorption feature-based identification relies in most application cases on single REEs (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Turner et al 11 , Boesche et al 12 and Neave et al 9 successfully identified and mapped REEs using laboratory-or ground-based hyperspectral imaging (HSI). Booysen et al 3 demonstrated how unmanned aerial vehicle (UAV)-based hyperspectral data can be used in a multi-scale remote sensing exploration approach to map REEs indirectly. Minute spectral features, low concentrations, large ground sampling distances (GSDs) and heavy imaging equipment have impeded their direct measurements from lightweight airborne platforms so far.…”
mentioning
confidence: 99%
“…Drones have been increasingly used in mineral exploration (e.g., Booysen et al 3 ; Jackisch et al 13 ; Malehmir et al 14 ; Sayab et al 15 ). Difficult terrain or outcrops unreachable on foot or by vehicles can be rapidly surveyed with UAVs from a safe distance with minimal personnel on site, ensuring safety, efficiency and speed 16,17 .…”
mentioning
confidence: 99%
See 1 more Smart Citation